Some developments of Upper Permian beds in the area west of Škofja Loka (Western Slovenia) - Demšar, Matevž; Dozet, Stevo (Geologija, 2002)
The article deals with three cross-sections of the Upper Permian beds in the area west of Škofja Loka. On the western slope of the Križna gora there is a limestone-dolomite development of the Upper Permian series. The limestone-dolomite development is exposed in the village Planica area at Čepulje as well. However, the most complete development of the Upper Permian can be followed in the Zadnja Smoleva valley.